Innovation management process in the biomass generation from microalgae - Cruz, Conrado Aguilar; Herrera, Moises Manzano; Briseño, Gerardo Ballesteros (IJRDO - Journal of Business Management, 2019)
The aim of this of this study is to examine the dimensions of innovation management to explain, from a strategic perspective, the process in the development of innovative projects applied to cultivation systems for the generation of algal biomass. The employed methodology incorporates dynamic change contexts, generating high uncertainty in organizational decision-making. Managing innovation in renewable energies implies a structured and systemic process that includes technological surveillance, competitive intelligence, foresight, and planning. The results show that technological surveillance offers the possibility of making progress on border knowledge in the design, manufacturing and instrumentation of photobioreactors for the microalgae culture. It is concluded that the costly process for the generation of renewable energies for human consumption leads to reflect on its viability before being available for use, especially the management of those actions aimed at creative solutions.